2015
DOI: 10.1097/aud.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Perception and Production of Speech Feature Contrasts by Pediatric Implant Users

Abstract: The finding of greater production than auditory perception accuracy for five of the six features examined suggests that the children with CIs were able to produce articulatory contrasts that were not readily perceived through audition alone. Factors that are likely to play a role in the greater production accuracy in addition to audition include the lexical and phonetic properties of the words elicited, a child's phonological representation of the words and motor abilities, and learning through oro-tactile, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Por outro lado, também é importante ressaltar que os participantes utilizaram dispositivos tecnológicos de acesso aos sons da fala e participaram de programa de reabilitação auditiva, possibilitando que aqueles com maiores escores de PCC e de PCC-r atingissem grau de inteligibilidade de fala "Boa". Esses achados concordam com pesquisas que destacam o impacto desses fatores na produção de fala (6,24,25) .…”
Section: Discussionunclassified
“…Por outro lado, também é importante ressaltar que os participantes utilizaram dispositivos tecnológicos de acesso aos sons da fala e participaram de programa de reabilitação auditiva, possibilitando que aqueles com maiores escores de PCC e de PCC-r atingissem grau de inteligibilidade de fala "Boa". Esses achados concordam com pesquisas que destacam o impacto desses fatores na produção de fala (6,24,25) .…”
Section: Discussionunclassified
“…The accuracy of consonant, consonant cluster and vowel production was assessed using a picture-naming task. This task has proved to reliably assess a child's ability to produce phonological contrasts in natural linguistic context (Edwards & Beckman, 2008;Mahshie et al, 2015). The picture-naming task used in this study was taken from the French EULALIES battery (Meloni et al, 2017).…”
Section: Picture-naming Taskmentioning
confidence: 99%
“…A follow-up study found that children with CIs produced less acoustic contrast between /s/ and /ʃ/ than children with NH, with /ʃ/-initial words being judged more intelligible than /s/-initial words (Reidy, Kristensen, Winn, Litovsky, & Edwards, 2017). Studies analyzing the speech of children with CIs using narrow transcription also provide evidence for fricative production confusions, particularly /ʃ/ substituting for /s/ (Baudonck, Dhooge, D'haeseleer, & Van Lierde, 2010;Mahshie, Core, & Larsen, 2015).…”
Section: Listening and Speaking With A CImentioning
confidence: 99%